Achieving Sustainable Development Goals by Wastewater Management: Review (Eurasian Journal of Engineering and Technology, 2023)
Today, the world aspires to reach sustainable development goals (SDGs) endorsed by the United Nations, and assessing the fundamental interest of modernistic technology in achieving the SDGs is very important for planners as well as stakeholders, which will permit them to defeat many of the problems and challenges we encounter in our world. In this study, the role of water sector management represented by wastewater in achieving the goals of sustainable development was clarified. An in-depth analysis of the goals and their interactions with each other reveals that wastewater treating can participate in implementing eleven of the seventeen sustainable development goals due to its capability to raise the amount of water available. We mention some examples of these goals: eradicating poverty and famine, clean water, promoting health, economic growth, waste recycling, clean energy, reducing the environmental impact of water sanitation and climate change, and others. We discussed the difficulties associated with implementing these goals, by proposing a series of indicators to evolve importance of wastewater treatment plants in SDGs. The current review article confirmed the considerable impact of wastewater treatment on achieving the internationally approved SDGs